Towards a long-term model construction for the dynamic simulation of HIV infection - M. Hadjiandreou; Raul Conejeros; Vassilis S. Vassiliadis (Mathematical Biosciences and Engineering)
This study involves the mathematical modelling of long-term HIV dynamics.The proposed model is able to predict the entire trajectory of the disease:initial viremia in the early weeks of the infection, latency, and progressionto AIDS; a range spanning approximately ten years. The model outcomes were comparedto clinical data and significant agreement was achieved. The formulatedmodel considers all important population compartments including macrophages,latently-infected CD4+ T-cells, and cytotoxic T-lymphocytes (CTLs),an attempt which in many respects is novel in the area of HIV modelling.The ranges of the model parameters and initial conditions were obtainedfrom literature, and their values were determined in this work directlyby fitting published clinical data. Furthermore, the simulation resultsemphasize the importance of macrophages in HIV infection and progressionto AIDS and show a clear correlation between the level of CTLs andHIV progression. The ability of the model to correlate analyticaldata gives credibility to its predictions, a fact that will beexploited in future research in modelling immunological and pharmacologicalavenues of treatment.